Examination the users’s opinion of the electronic submission programme - Cseh, András (Acta Agraria Debreceniensis, 2009)
In Hungary the Agricultural and Rural Development Agency (ARDA) started to introduce electronic filling and submission of application forms for the two-hundred-thousand farmers in 2008. For submission it is recommended to be registered using by client gate. The producers’ benefits have more results from electronic filling. Filling in and submitting the applications electronically ensure data will be correct and the application technically flawless and this can be the basis on the payment of former financial support and avoidance of sanctions or subtractions due to technical faults. The farmers may ensure the money more quickly. Based on survey is analysed the users of system conceive of the electronic submission programme.